Integrated Water Resources Management and Security in the Middle East - Lipchin, Clive; Pallant, Eric.; Saranga, Danielle; Amster, Allyson; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2007)
Integrated Water Resources Management and Security in the Middle East brings together diverse voices relating to the critical issue of water management in one of the world’s most politically volatile areas: the Middle East. The book brings together Palestinian, Israeli, Jordanian and international expert opinions on creating a holistic and comprehensive view of water management challenges and strategies in an area of conflict and resource scarcity. The book takes security studies to the next level beyond military preparedness to address the security implications of the most fundamental of resources, that of water. Indeed, the book delves deeply into the underlying ideological underpinnings of various water regimes and possible opportunities for new decision-making models and regional cooperation. This book serves an important place in the scholarly literature on this topic for its breadth of participants and perspectives and its concrete steps forward. It moves the academic discourse beyond pointing fingers and toward constructive solutions and dialogue.
Retelling the Story of Water in the Middle East: Reflections on and about a Conversation at the Dead Sea -- Retelling the Story of Water in the Middle East: Reflections on and about a Conversation at the Dead Sea -- Water Resources in the Middle East -- Fresh Water in the Middle East and North Africa -- Water Development for Israel: Challenges and Opportunities -- Water and Security in Jordan -- Water and Security for Palestine -- Policy and Management Options -- Environment and Security in the Middle East: Conceptualizing Environmental, Human, Water, Food, Health and Gender Security -- Hydro-Diplomacy: Opportunities for Learning from an Interregional Process -- Perspectives on Alternative Water Sources in Europe and the Middle East -- International Water Law and Implications for Cooperative Israeli-Palestinian Transboundary Water Management -- Engendering Water in the Middle East: Some Preliminary Thoughts -- Water, Agriculture and Zionism: Exploring the Interface Between Policy and Ideology -- Trading the Rain: Should the World's Fresh Water Resources be an Internationally Traded Commodity? -- Case Studies -- Transboundary Stream Restoration in Israel and the Palestinian Authority -- Scenarios for a more Sustainable Water Management in the Dead Sea Basin -- Creating a Sustainable Future for Israelis and Palestinians.
Keywords: Environmental management; Water pollution; Nature; Environment; Environmental economics; Economic geography; Environmental Management; Water Policy/Water Governance/Water Management; Waste Water Technology / Water Pollution Control / Water Management / Aquatic Pollution; Popular Science in Nature and Environment; Environmental Economics; Economic Geography